(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2026)
Background: Laparoscopic inguinal hernia repair has become an increasingly accepted approach in paediatric surgery. Among the minimally invasive techniques, intracorporeal suturing and percutaneous extracorporeal suturing are widely practiced, yet debate remains regarding their comparative outcomes. Objective: To compare the outcomes of intracorporeal suturing and percutaneous extracorporeal suturing techniques in laparoscopic inguinal hernia repair in children. Methods: This study was conducted in the Department of Paediatric Surgery, Dhaka Medical College Hospital, from September 2022 to February 2024. A total of 131 male children aged 2–12 years with clinically diagnosed inguinal hernia were enrolled and randomly allocated into two groups: Group A (intracorporeal suturing, n=65) and Group B (extracorporeal suturing, n=66). Operative time, per‑operative and post‑operative complications, and short‑term outcomes were analysed. Statistical analysis was performed using SPSS. Results: The mean age of patients was comparable between the two group, mean age was 6.22 ± 1.90 years in Group A and 6.05 ± 2.53 years in Group B, showing no statistically significant difference. The mean duration of surgery was significantly longer in Group A compared to Group B (p<0.001). No significant difference was observed between the groups regarding intra‑operative complications, postoperative hydrocele, testicular atrophy, or recurrence during follow‑up. Both techniques were found to be safe and effective. Conclusion: Percutaneous extracorporeal suturing is a safe, effective, and time‑saving alternative to intracorporeal suturing in laparoscopic inguinal hernia repair in children, with comparable complication rates and favourable outcomes. Journal of Paediatric Surgeons of Bangladesh (2024) Vol. 15 (1 & 2): 29-32